DURÛS AL-LUGHAH AL-‘ARABIYYAH KARYA MAHMUD YUNUS DALAM PERSPEKTIF NAZARIYYAH AL-WAHDAH - M. Yusuf Salam (Ta'dib, 2008)
Durus Al-Lughah Al- Arabiyah (DLA) is one out of 72 works of Mahmud Yunus. This book consists of four series in which the approach of Nazariyyah Al-Wahdah  was applied. This approach deals with taking themes or texts as the main or center for learning activities of Arabic: sounds, vocabulary, grammar, literature and media use. These five aspects were used by Mahmud Yunus in DLA. The concurrence of DLA and approach of Nazariyyah Al-Wahdah was achieved by making materials related one another.Kata Kunci: nazariyyah- Al-wahdah